CAPITAL BUDGETING ANALYSIS OF DOOR-TO-PORT CONTAINER TRAIN TRANSPORT FROM GEDEBAGE CONTAINER TERMINAL TO JICT PORT PROJECT - Hartasantoso, Fakhrul
The Indonesian government issued Presidential Instruction No. 5 of 2020 regarding the National Logistics Ecosystem (NLE) arrangement which outlines four action plans including an activity to synchronization of container railway routes. The initial activity target is extending the railway line to Pasoso Port or JICT Port but it will interfere with the existing truck operations. So, the party involved decide for the implementation of Presidential Instruction No. 5 of 2020, the quick win is Doorto-Port Container Train Transport from the Gedebage container terminal to JICT Port Project. Regarding the quick win, this research aims to analyze the feasibility of the project for KAI.